Terapi anti-koagulan pada pasien pasca bedah katup - Ali Syahputra; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2010)
The development of valvular surgery has enabled many patients to lead active and useful lives. Prosthetic heart valves improve quality of life and survival of patients with severe valvular heart disease, but the need for antithrombotic therapy to prevent thrombotic complications in valve recipients poses challenges for clinicians and patients. Advances in antithrombotic therapy and valve technologies are likely to improve the management of patients with heart valves surgery.